Malware Static Analysis on Microsoft Macro Attack - Aresta, Redho Maland; Pratomo, Ero Wahyu; Geraldino, Vicky; Fauzi, Achmad; Santoso, Joko Dwi (Mobile and Forensics, 2021)
In the 21st century, technology is increasing rapidly, the increase in technology is the potential for cyber attacks on today's technological infrastructure. Malware that is designed to damage computer systems without the owner's knowledge at a considerable cost becomes a cyber crime. This macro malware analysis is to study the code and behavior of malware when run on an operating system. To analyze this malware, this study uses a static analysis method by analyzing malware without running the program.